The Implementation of The Quizizz Application in Improving Students’ Motivation and Learning Outcomes in Mathematics - Subayil; Shahibul Ardhi; Husnul Khotimah (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
This study aims to examine the implementation of the Quizizz application in improving students’ motivation and learning outcomes in mathematics. The research employs the Systematic Literature Review (SLR) method by analyzing relevant scientific articles published between 2019 and 2022. The articles were obtained from Google Scholar, Garuda, and Google Search. The results of the review indicate that the use of Quizizz as a game-based learning medium has a positive impact on students’ motivation, interest, and learning outcomes. Interactive features such as instant feedback, leaderboards, and engaging visual displays create a more enjoyable learning environment and encourage active student participation. In addition, Quizizz helps students understand mathematical concepts more easily. However, its implementation still faces several challenges, including dependence on internet connectivity and limited supporting facilities. Despite these limitations, Quizizz is considered an effective and innovative learning medium that can enhance the quality of mathematics learning and promote active student engagement. The findings of this study are expected to serve as a reference for educators in selecting innovative teaching strategies and as a foundation for developing technology-based learning in the future.